Análise da relação entre a cooperação e o desempenho internacional mediada pelas capacidades dinâmicas de internacionalização - Diniz, Adriana G. Fabrini (2018)
The motivation for this thesis was to analyze how the Cooperation, through the Dynamic Capacities of Internationalization contributes to the International Performance of internationalized companies installed in the State of Paraná. Using the mixed method of research, the first step - quantitative - was done through the application of a questionnaire to 158 companies, whose data were analyzed by the statistical techniques of Analysis of Agglomerates and Structural Equation Modeling (SEM). The results obtained in this stage showed that the internationalized companies of Paraná are segmented into three groups, depending on the level of cooperation with third parties. These agglomerates were denominated: Operational Cooperation, Tactical Cooperation, and Strategic Cooperation, whose main indicator that distinguish them is the number of shared assets. The companies that make up these three clusters share, on average, one, three and eight assets, respectively. From this segmentation, the impact of the Cooperation on International Performance was measured. It was found that the migration from 1 to 8 shared assets increases the export performance by 35.7% and the performance in Foreign Direct Investment (FDI) by 183.3%. Through the SEM, it was verified that the Dynamic Capacities of Internationalization intervene in the relation between Cooperation and International Performance, specifically, for companies that realize FDI. Subsequently, for the qualitative step, five companies were selected by the membership, whose interviews were analyzed through Content Analysis. This step was representative in order to complement the results obtained through the statistical analyzes. Through the Content Analysis, it was noticed that internationalization is not the strategic focus of the five companies surveyed. As the theory holds, some companies internationalize themselves through opportunities that the market presents to them and others in a strategically planned way. Being that, those that are internationalized in a planned way, are the same that obtain the greater benefits of this activity. The sample interviewed was not prone to the achievement of FDI, mainly because it is a strategy that requires greater investments and, consequently, greater risks. The interview's analysis allowed us to understand that the relationship that organizations maintain with other companies - Cooperation - plays an important role in the processes of internationalization, as it helps in the improvement of internal processes that reflected in the international competitiveness. Some companies are aware of the role of cooperation, especially those that have internationalization as a strategic goal.